2003
DOI: 10.1248/yakushi.123.25
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy with Hybrid Liposomes without Any Drug <i>in Vivo</i>

Abstract: Prolonged survival was seen in a carcinoma model in mice intraperitoneally inoculated with B-16 melanoma cells after the intraperitoneal treatment with hybrid liposomes composed of L-a-dimyristoylphosphatidylcholine (DMPC) and polyoxyethylenedodecyl ether (C 12 (EO) n , n=10 and 23 respectivery) which had a uniform and stable structure. No drug was administered. The therapeutic eŠects of the single-component liposomes composed of lipids with a variety of hydrophilic head groups and diŠerent hydrophobic alkyl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…In the previous paper, we indicated the same biodistribution of NBD-HL except skeletal muscle in the normal mice. 29) These results suggest that HL could be metabolized in liver, and the toxicities of GM to kidney and auditory nerve systems could be suppressed by using HL as the drug carrier.…”
Section: Discussionmentioning
confidence: 93%
“…In the previous paper, we indicated the same biodistribution of NBD-HL except skeletal muscle in the normal mice. 29) These results suggest that HL could be metabolized in liver, and the toxicities of GM to kidney and auditory nerve systems could be suppressed by using HL as the drug carrier.…”
Section: Discussionmentioning
confidence: 93%
“…We have already reported that HL and cationic HL have no side-effects in vivo in the safety tests intravenously administered via a vein using mice 9,21) and rats. [17][18][19] These results indicate that cationic HL could not have severe side effects.…”
Section: Autopsy Analysis Of the Hepatic Metastasismentioning
confidence: 85%
“…16 21 , 65.7 mg/kg/d for 2C 14 ECl) were intravenously administered once each day for 14 d. Safety of 136 mg/kg/d for DMPC in chronic toxicity test using mice and rats has been reported. [17][18][19] After 14 d, the livers were isolated from the mouse models, fixed in 10% formalin solution, embedded in paraffin and sectioned at 5 µm of thickness. The liver sections were stained with hematoxylin and eosin (H&E) and observed by an optical microscope (Nikon TS-100, Tokyo, Japan).…”
Section: Preparation Of Hybrid Liposomesmentioning
confidence: 99%
“…9) (d) No toxicity of the hybrid liposomes was observed in normal cells in vitro nor in normal rats in vivo. 8,10) In this study, we report on hybrid liposomes composed of L-a -dimyristoylphosphatidylcholine (DMPC) and polyoxyethylenedodecyl ether (C 12 (EO) n : CH 3 (CH 2 ) 11 O(CH 2 CH 2 O) n H) having inhibitory effects on the growth of human breast tumor cells (MDA-MB-453) in vitro along with apoptosis.Hybrid liposomes were prepared by sonication (VELVO VS-N300, 300W) of a mixture containing 95 mol% DMPC and 5 mol% C 12 (EO) n in 5% glucose solution at 45°C with 300W, followed by filtration with a 0.20 mm filter.First, we examined the fifty percent inhibitory concentration (IC 50 ) of hybrid liposomes (HL-n) on the growth of MDA-MB-453 cells in vitro on the basis of WST-1 assay. …”
mentioning
confidence: 99%
“…9) (d) No toxicity of the hybrid liposomes was observed in normal cells in vitro nor in normal rats in vivo. 8,10) In this study, we report on hybrid liposomes composed of L-a -dimyristoylphosphatidylcholine (DMPC) and polyoxyethylenedodecyl ether (C 12 (EO) n : CH 3 (CH 2 ) 11 O(CH 2 CH 2 O) n H) having inhibitory effects on the growth of human breast tumor cells (MDA-MB-453) in vitro along with apoptosis.…”
mentioning
confidence: 99%